Left ventricular cardiac geometry and ambulatory blood pressure in children. Issue 5 (13th April 2019) - Shilly, Steffi; Merchant, Kumail; Singer, Pamela; Frank, Rachel; Gurusinghe, Shari; Infante, Lulette; Sethna, Christine B.
Abstract: Limited information is available regarding the relationship between ambulatory blood pressure monitoring (ABPM) and cardiac geometry in hypertensive children. ABPM and 2D‐echocardiography were retrospectively reviewed in children and adolescents <21 years old with primary hypertension. A total of 119 participants (median age 15.0 [IQR 12, 16] years) with hypertension were included. Left ventricular hypertrophy was diagnosed in 39.5% of participants. Normal geometry was found in 47.1%, concentric remodeling (CR) in 13.4%, concentric hypertrophy (CH) in 15.1%, and eccentric hypertrophy (EH) in 24.4% of children. After adjustment for age, sex, and body mass index z‐score, awake systolic blood pressure (BP) index (BPi) (OR 1.07, 95% CI: 1.001‐1.14, P  = 0.045), awake diastolic BPi (OR 1.04, 95% CI: 1.00‐1.09, P  = 0.048), awake systolic BP load (OR 1.02, 95% CI: 1.000‐1.04, P  = 0.047), and sleep systolic BP load (OR 1.02, 95% CI: 1.001‐1.04, P  = 0.03) were directly associated with CH. No ABPM parameters were significant predictors of EH. In conclusion, ABPM parameters were found to be independent predictors of cardiac geometry, specifically CH.